O acirramento da pressão estética direcionada às mulheres na contemporaneidade: uma leitura fenomenológico-hermenêutica - Oliveira, Gabriela Barcellos de (2022)
The historic association between beauty and woman gains new – and intense – connotations in the contemporary setting. This is a finding woven by studies, research, and clinical observations, which point to a vertiginous increase in the suffering experienced by girls and women in the face of certain aesthetic impositions. With this in mind, the present theoretical work aimed to explain and clarify the ontological bases that made possible the aggravation of the aesthetic pressure directed at women in the contemporary world. The understanding of this phenomenon results from the application of the phenomenological-hermeneutic method as proposed by Martin Heidegger - a philosopher who considers existing as a human as being-there and being-in-the-world, therefore articulating what is shown to one’s field of apparition. The objective of this dissertation was, thus, to understand the current relationship between women and their appearance not from a singularized reading of sufferings, but from the historical event that structures the current time: the technique. Through the course of this dissertation, it is shown that in an era traversed by technique as the truth of being, an enormous effort is made in an attempt to dominate and control phenomena, with little room left for unveiling, for not-knowing. The existential uprooting promoted by this spirit proved to be fertile ground for an unbridled and violent adherence to contemporary mundane imperatives – which vocalize assertive directions about “correct” ways of existing, demanding performance and individual improvement at all costs. The present work considers, ultimately, that the aesthetic impositions directed at girls and women, in the way they present themselves in the current scenario, can indeed be taken as another form of violence directed at them